The Impact of Macroeconomic Conditions on the Instability and Long-Run Inequality of Workers’ Earnings in Canada - Beach, Charles; Finnie, Ross; Gray, David (Relations industrielles / Industrial Relations, 2005)
This paper examines the variability of workers’ earnings in Canada over the period 1982‑1997. Using a large panel of tax file data, we decompose total variation in earnings across workers and time into a long-run inequality component between workers and an average earnings instability component over time for workers. We find an increase in earnings variability between 1982‑89 and 1990‑97 that is largely confined to men and largely driven by widening long-run earnings inequality. Second, the pattern of unemployment rate and GDP growth rate effects on these variance components is not consistent with conventional explanations and is suggestive of an alternative paradigm of how economic growth over this period widens long-run earnings inequality. Third, when unemployment rate and GDP growth rate effects are considered jointly, macroeconomic improvement is found to reduce the overall variability of earnings as the reduction in earnings instability outweighs the widening of long-run earnings inequality.